An Optimization Scheme of Test Performance Improvementfor AC Drive Test System - WANG Pengkui; ZHOU Xiaoling; CHENG Hao; WANG Yimin; XU Weizhuan (Kongzhi Yu Xinxi Jishu)
Products of traction drive system have the characteristics of high switching frequency and high efficiency. In order to evaluate the product performance more accurately, the bandwidth and precision of AC drive test system are required to be higher. In this paper, the signal characteristics, test difficulties and efficiency test problems in the application of AC drive test system are described in detail. Through the optimization and improvement of hardware sensor precision and bandwidth, software conditioning circuit precision and data processing algorithm, the relative error of test eigenvalue is controlled within 0.4%, and the test results show that the accuracy of the system is obviously improved.